Pendampingan Kajian Kitab At Tibyan Fi Adabi Hamalati Qur'an Terhadap Peningkatan Akhlak Santri Di Pondok Pesantren Azzainuriyah Dzarut Dzakirot Cukir - Khumairoh An Nahdliyah; Desy Naelasari; Arif Rahman Hakim; Muhammad Anas Ma'arif; Ferry Yanto (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2025)
Memorizers of the Qur'an play a very important role in maintaining, spreading, and practicing the teachings of the Qur'an. However, to become memorizers who not only memorize the text, but also understand and practice it in everyday life, they need in-depth guidance and knowledge. One of the books that is very relevant to this study is At-Tibyan fi adabi hamalati Al-Qur'an by Imam An-Nawawi. This book provides very useful guidance for memorisers of the Qur'an in maintaining the manners and ethics that must be applied in their lives as carriers and memorizers of the Qur'an. Guidance is needed in the study of the book At-Tibyan fi adabi hamalati Al-Qur'an to improve the understanding and application of the morals of students. The methods in this guidance are the sorogan, bandongan and mudzakaroh methods as well as interactive discussions and direct practice in everyday practice. The results of this book study assistance are an increase in students' understanding of the etiquette of carrying the Qur'an, the formation of noble morals in everyday life, an increase in awareness of responsibility as memorisers of the Qur'an, an increase in students' motivation to learn, an increase in the ability to implement the values of the book, and a strengthening of the tradition of knowledge in Islamic boarding schools. The obstacles faced are a lack of motivation and interest in learning, varying levels of understanding and difficulties in practicing the contents of the book